Liver Transplantation for Alcoholic Hepatitis: Standard of Care Yet? - Cracco, Alejandro; Montorfano, Lisandro; Vanatta, Jason M. (Digestive Disease Interventions, 2020)
Alcohol-related liver disease (ALD) is one of the most common indications for liver transplantation. However, liver transplantation for alcoholic hepatitis (AH) remains controversial. The morbidity of severe alcoholic hepatitis (SAH) is extremely high, with most of the deaths occurring within the first 2 months. Multiple studies have recently demonstrated significant improvement in overall survival following liver transplantation in patients with SAH who failed medical management, with comparable rates to those transplanted electively. Concerns remain due to the small pool of donors and the high risk of alcohol relapse in this population. The traditional requirement of 6 months of abstinence prior to transplantation, or also known as “6-month rule” is controversial and has been criticized as whether it is a good predictor of long-term sobriety. Previous studies among patients with alcoholic cirrhosis have indicated that this rule poorly identifies patients who will relapse after liver transplantation. More recent studies in patients transplanted for SAH, have reported relapse rates that are comparable to those with abstinence periods >6 months. Applying stringent selection criteria appears to be key in identifying patients who are less likely to relapse after transplantation, and therefore prolonging patient and graft life. However, further research is needed to identify patients at risk and create appropriate screening tools. In this article, we present a review of currently available data on this topic.
Keywords: liver transplantation; alcohol-related liver disease; review